Remimazolam in pediatric anesthesia: a systematic review for clinical decision-making - Zhang, Yi; Chen, Qiuxiang; Wang, Linyun; Zeng, Qingjun; Cui, Haishan; Guo, Shuang; Xiang, Fei; Mo, Yunbo (Frontiers in Pediatrics, 2025)
BackgroundRemimazolam's role in pediatric anesthesia is evolving. We systematically reviewed 2024–2025 evidence to establish a clinical decision-making framework for its use.MethodsFollowing PRISMA guidelines, a systematic search identified 23 studies (15 RCTs) involving 2,847 pediatric patients for narrative synthesis.ResultsRemimazolam demonstrated superior hemodynamic stability vs. propofol (cardiovascular complications: RR 0.30, 95% CI 0.20–0.46) and reduced emergence delirium by 61% (RR 0.39, 95% CI 0.21–0.70). The CES1 G143E polymorphism was identified as a genetic basis for prolonged sedation, reducing drug clearance >90%. Critical limitations include a 15% re-sedation rate post-flumazenil, a complete lack of data in infants <1 year, and unknown long-term neurodevelopmental safety.ConclusionRemimazolam represents a valuable anesthetic tool with specific advantages in pediatric anesthesia. While it demonstrates superior hemodynamic stability and reduced emergence delirium compared to standard agents, it is not a universal replacement for established anesthetics. Current evidence supports its use in specific clinical scenarios, particularly for preventing post-sevoflurane emergence delirium and in hemodynamically unstable patients. However, the absence of infant and long-term neurodevelopmental safety data necessitates continued research before widespread adoption.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD420251058023, PROSPERO CRD420251058023.